Chiral non-stoichiometric ternary silver indium sulfide quantum dots: investigation on the chirality transfer by cysteine. Issue 33 (15th August 2022) - Branzi, Lorenzo; Purcell-Milton, Finn; Cressoni, Chiara; Back, Michele; Cattaruzza, Elti; Speghini, Adolfo; Gun'ko, Yurii K.; Benedetti, Alvise
Abstract : Ligand-induced chirality in ternary non-stoichiometric silver indium sulfide (AIS) QDs is observed for the first time by the isolation of l - AIS and d - AIS QDs stabilized with l - or d -cysteine, respectively. Abstract : Chiral semiconductor quantum dots have recently received broad attention due to their promising application in several fields such as sensing and photonics. The extensive work in the last few years was focused on the observation of the chiroptical properties in binary Cd based systems. Herein, we report on the first evidence of ligand-induced chirality in silver indium sulfide semiconductor quantum dots. Ternary disulfide quantum dots are of great interest due to their remarkable optical properties and low toxicity. Non-stoichiometric silver indium sulfide quantum dots were produced via a room temperature coprecipitation in water, in the presence of cysteine as a capping agent. The obtained nanocrystals show a notable photoluminescence quantum yield of 0.24 in water dispersions. Several critical aspects of the nanocrystal growth and chemico-physical characterization, and the optimisation of the surface passivation by the chiral ligand in order to optimize the nanoparticle chirality are thoroughly investigated. Optical spectroscopy methods such as circular dichroism and luminescence as well as nuclear magnetic resonance techniques are exploited to analyze the coordination processes leading to the formation of the ligand–nanocrystal chiral interface. This study highlights the dynamic nature of the interaction between the nanocrystal surface and the chiral ligand and clarifies some fundamental aspects for the transfer and optimization of the chiroptical properties.